Distinct anthropogenic aerosol and greenhouse gas effects on El Niño/Southern Oscillation variability - Xianglin Ren; Wei Liu (Communications Earth & Environment)
Abstract El Niño/Southern Oscillation variability has conspicuous impacts on ecosystems and severe weather. Here, we probe the effects of anthropogenic aerosols and greenhouse gases on El Niño/Southern Oscillation variability during the historical period using a broad set of climate models. Increased aerosols significantly amplify El Niño/Southern Oscillation variability primarily through weakening the mean advection feedback and strengthening the zonal advection and thermocline feedbacks, as linked to a weaker annual cycle of sea surface temperature in the eastern equatorial Pacific. They prevent extreme El Niño events, reduce interannual sea surface temperature skewness in the tropical Pacific, influence the likelihood of El Niño/Southern Oscillation events in April and June and allow for more El Niño transitions to Central Pacific events. While rising greenhouse gases significantly reduce El Niño/Southern Oscillation variability via a stronger sea surface temperature annual cycle and attenuated thermocline feedback. They promote extreme El Niño events, increase SST skewness, and enlarge the likelihood of El Niño/Southern Oscillation peaking in November while inhibiting Central Pacific El Niño/Southern Oscillation events.